The Impact Of Organizational Culture On Employee Performance With Job Satisfication As A Mediation Variable: (Case Study At Bank Indonesia Representative Office Lampung Province) - W. S, Dyah Etika; Erlina, RR.; Mardiana, Nova (Jurnal Economic Resource, 2025)
This study uses a quantitative approach with the Structural Equation Modeling Partial Least Square (SEM PLS) analysis method. Data were collected by distributing questionnaires to all employees of the Bank Indonesia KPw Lampung Province with a sample of 126 employees, then analyzed using SmartPLS software to test the direct and indirect effects between variables. The results of the study indicate that organizational culture has a positive and significant effect on employee performance, organizational culture has a very strong and significant effect on job satisfaction and job satisfaction significantly mediate the influence of organizational culture on employee performance. This shows that part of the influence of organizational culture on employee performance is channeled through job satisfaction (partial mediation). This finding confirms the importance of strengthening organizational culture and increasing job satisfaction to support the achievement of optimal performance which can ultimately improve employee performance at the Bank Indonesia Representative Office of Lampung Province